The Conceptual Metaphor of the Road in the Lithuanian Election Discourse - Cibulskienė, Jurga (Kalbotyra, 2005)
The present article focuses on the 2000 election discourse in Lithuania on the basis of conceptual metaphor theory within the framework of cognitive linguistics. Assuming that conceptual metaphor is pervasive in everyday life, not just in language but in thought and action, the article investigates the conceptual metaphor POLITICS IS A JOURNEY in the election discourse of the Conservative Party and Social-democratic Coalition. The results revealed that both political parties used this metaphor but put emphasis on different things. The Conservative party foregrounded the goal of the journey to be achieved – the European Union and NATO – while the Social-democratic Coalition underlined overcoming of obstacles on the road. According to the realisation character of the conceptual metaphor in different discourses, we can judge about real aims and attitudes of the politicians.